Interannual variation of imposex in the sea snail Thaisella chocolata (Muricidae) on the central coast of Peru - Iannacone, José (2023)
The hormonal alteration generated by tributyl (TBT) in female gastropods causes sterility due to the imposex phenomenon. The aim of this study was to characterize the annual variation of imposex in the sea snail Thasiella chocolata (Muricidae) in seven locations on the central coast of Peru. A unit of 1188 samples of T. chocolata were evaluated between 2013 and 2016. The imposex cataloging was evaluated based on the following indicators: imposex in females (I%), Relative Penile Length Index (RPLI), the Relative Penile Size Index (RPSI) and the Vas Deferens Sequence Index (VDSI). The global percentage of Imposex of 36.39% was observed, and a downward trend from 2013 to 2016 in the percentage of Imposex, RPLI, RPSI and VDSI. The percentage of Imposex according to locality varied between 5.88 to 52.10%. The severity indices based on the RPLI and RPSI by locality presented the following sequence: Chorrillos > Pucusana > San Bartolo > Isla San Lorenzo > Agua Dulce > La Punta > Callao; and for the VDSI it was: Pucusana > La Punta = San Bartolo = San Lorenzo Island > Chorrillos > Agua Dulce > Callao. There was evidence of a reduction in the length of the penis of females, and of the RPLI of T. chocolata between the years of evaluation.